Реализация ключевых идей модульных программ на уроке: проблемы, опыт, перспективы - Кудинова, Л. Н. (My University, 2016)
The article gives examples of changes in school practices through the introduction of new approaches to teaching geography. The effectiveness of the key ideas of modular programs in terms of interest in the subject and the quality of education.
Keywords: dialogical learning; cooperation; group form of work; innovation; socialization